(untitled) (Journal of Partial Differential Equations, 2018)
In this paper, by using a semimartingale approximation of a fractional stochastic integration, the global Harnack inequalities for stochastic retarded differential equations driven by fractional Brownian motion with Hurst parameter 0 ‹ H ‹ 1 are established. As applications, strong Feller property, log-Harnack inequality and entropycost inequality are given.